A contemporary strain of RSV activates primary human monocytes after abortive infection - Agac, Ayse; Ludlow, Martin; Knittler, Marie-Christin; Prajeeth, Chittappen Kandiyil; Saletti, Giulietta; Osterhaus, Albert D. M. E.; Meineke, Robert; Rimmelzwaan, Guus F. (Frontiers in Immunology, 2025)
Respiratory syncytial virus (RSV) is a leading cause of lower respiratory tract infections worldwide, particularly affecting infants, older adults, and immunocompromised individuals. Understanding the cellular immune response to RSV infection is essential for developing effective treatments for infection and its complications. In this study, we investigated the susceptibility of blood-derived primary monocytes and monocytic THP-1 cells to infection with a contemporary RSV A-ON1 strain and characterized the subsequent cytokine and chemokine secretion, as well as the expression of surface markers involved in antigen presentation. Our findings demonstrate that primary monocytes and related THP-1 cells are permissive to abortive infection by RSV, leading to increased expression of proinflammatory cytokines and chemokines, including IP-10, IL-6, and CCL2. Furthermore, primary monocytes expressed CD80, CD86, and HLA-DR upon direct infection or through potential paracrine stimulation. Collectively, these findings demonstrate the activation of monocytes by RSV infection, suggesting their contributory role in orchestrating early immune responses during infection.